Reposisi Ekspor Provinsi Kepulauan Riau Sebelum dan Saat Terjadinya Pandemi Covid’ 19 Tahun 2018 – 2020 - Akhirman Akhirman (Bahtera Inovasi, 2021)
This study aims to committee government policies in an effort to make policies on the Export Repositioning of Riau Islands Province in 2019-2020 or before and during the Covid19 outbreak and government policies on the national and regional economies in Indonesia. The data used to analyze this research is secondary data, which is obtained from several agencies such as BPS Keepri, media on online pages that provide information about the economy that occurred during the Covid-19 pandemic in Indonesia and areas issued by the government. Especially for exporters and local governments who are more concerned with the health of the wider community by following the government's appeal in one way is to follow the lockdown until the implementation of the PSBB with the aim of preventing the chain of spread of the Covid-19 pandemic.